The rapid plasma reagin (circle) card test in biological false positive and leprosy sera - Garner, M. F. (1972)
The rapid plasma reagin (RPR) circle card and the Venereal Disease Reference Laboratory (VDRL) slide test results were compared on a group of sera known to show biological false positive (BFP) reactions to reagin detection tests for syphilis. The RPR test was more specific than the VDRL test on the sera selected, ie, it gave fewer false positive results than the VDRL test. However, in a group of presumed normal sera, the RPR test gave BFP reactions while the VDRL test gave none. The RPR test gave fewer BFP reactions than the VDRL test in 269 sera from patients with lepromatous leprosy.